Model of State Support for Industrial Parks as a Tool for Sustainable Development - Natalia Mozaleva; Marina Ivanova; Grigory Kulkaev (International Journal of Technology, 2023)
The study focuses on government support for industrial parks as tools for sustainable development in Russia and other countries. The work investigates the influence of industrial activities, particularly those within eco-industrial parks, on the economic, social, and environmental conditions of regions and the country as a whole. The authors examined the main forms of support, financing, and regulation of industrial park activities and identified problematic aspects of state support for them. The experience of state support for industrial parks in China, Germany, and the USA is analyzed. The main features, approaches, and development tools are highlighted. Based on the analysis, a revised model of state support for industrial parks was developed within the framework of the concept of sustainable development, which can be implemented in Russia. The model consists of three stages of support, which are initiated at various levels of government, impacting both the federal and regional levels, as well as the actions of private investors. It is proposed to increase the use of indirect state support, creating favorable conditions for private investors. This approach is expected to result in more efficient investment utilization, enhanced competitiveness of enterprises, and a shift towards an environmentally-focused approach in industrial parks.